Path Analytic Study of Factors Affecting Students’ Attitude towards Test-Taking in Secondary Schools in Afikpo Education Zone, Ebonyi State, Nigeria - Owan, Valentine Joseph; Bassey, Bassey Asuquo; Agurokpon, Daniel Clement (American Journal of Creative Education, 2020)
A structural equation modelling approach was used to analyse 32 factors affecting students’ attitudes towards test-taking in secondary schools. Data for the study were obtained from a sample of 1,276 students using the proportionate stratified random sampling technique. The instrument used for data collection was a Rating Scale on Factors Affecting Students’ Attitudes Towards Test-Taking (RSFASATTT). Findings of the study revealed a total of 21 factors that significantly affect students’ attitudes towards test-taking in secondary schools. Out of these significant factors, 14 had a positive effect while 7 factors negatively affected students’ attitudes towards test-taking. However, 11 factors were not significant predictors of students’ attitudes towards test-taking. Based on these findings, it was concluded that students’ attitudes towards test-taking are affected by several factors. These factors are either traceable to the students’ emotions, their family background, or the school environment. Based on this conclusion, recommendations and policy implications were made.